Aplicação da avaliação do ciclo de vida do produto pelas organizações com sistema de gestão ambiental certificado - Lafin, Margareth (2004)
These study aims to propose actions and presents the advantage for the organizations in conduction Life Cycle Assessment (LCA) as a supporting and decision making tool, in the implementation of an environmental management system (EMS). LCA shall be used to analyse the product Life Cycle from resources extraction (cradie) to final disposal (grave). The first chapters of the dissertation presents the possibilities to integrate LCA in current EMS, research of the state-of-art of certified brazilian organizations, tools adopted in EMS and inventory analisys and impact assessment. Finally, are presented LCA application and the environmental contribution regarding the product chain